A new synthetic access to 2-N-(glycosyl)thiosemicarbazides from 3-N-(glycosyl)oxadiazolinethiones and the regioselectivity of the glycosylation of their oxadiazolinethione precursors - El Ashry, El Sayed H.; El Tamany, El Sayed H.; Fattah, Mohy El Din Abdel; Aly, Mohamed R. E.; Boraei, Ahmed T. A.; Duerkop, Axel (Beilstein Journal of Organic Chemistry, 2013)
Glycosylations of 5-(1H-indol-2-yl)-1,3,4-oxadiazoline-2(3H)-thione delivered various degrees of S- and/or N-glycosides depending on the reaction conditions. S-Glycosides were obtained regiospecifically by grinding oxadiazolinethiones with acylated α-D-glycosyl halides in basic alumina, whereas 3-N-(glycosyl)oxadiazolinethiones were selectively obtained by reaction with HgCl2 followed by heating the resultant chloromercuric salt with α-D-glycosyl halides in toluene under reflux. On using Et3N or K2CO3 as a base, mixtures of S- (major degree) and N-glycosides (minor degree) were obtained. Pure 3-N-(glycosyl)oxadiazolinethiones can also be selectively obtained from glycosylsulfanyloxadiazoles by the thermal S→N migration of the glycosyl moiety, which is proposed to occur by a tight-ion-pair mechanism. Thermal S→N migration of the glycosyl moiety can be used for purification of mixtures of S- or N-glycosides to obtain the pure N-glycosides. The aminolysis of the respective S- or N-glycosides with ammonia in aqueous methanol served as further confirmation of their structures. While in S-glycosides the glycosyl moiety was cleaved off again, 3-N-(glycosyl)oxadiazolinethiones showed a ring opening of the oxadiazoline ring (without affecting the glycosyl moiety) to give N-(glycosyl)thiosemicarbazides. Herewith, a new synthetic access to one of the four classes of glycosylthiosemicarbazides was found. The ultimate confirmation of new structures was achieved by X-ray crystallography. Finally, action of ammonia on benzylated 3-N-(galactosyl)oxadiazolinethione unexpectedly yielded 3-N-(galactosyl)triazolinethione. This represents a new path to the conversion of glycosyloxadiazolinethiones to new glycosyltriazolinethione nucleosides, which was until now unknown.
Keywords: glycosyloxadiazolinethiones; glycosylsulfanyloxadiazoles; glycosylthiosemicarbazides; thermal rearrangement; X-ray crystallography